The Role of the Job Creation Law (Omnibus Law) on the Welfare of Female Workers in the Industries Organization - Santy, Santy (IJOSMAS, 2023)
The purpose of writing this article is to find out what are the impacts of the omnibuslaw on women workers. The method of writing this journal is to use a descriptive method with literature study techniques. Following the passing of the Job Creation Law, there are a number of things that are of course detrimental to various parties, for example workers and workers who are female. In the process of its implementation, the Job Creation Law makes women workers uneasy. Therefore, the government should review this law which is considered imperfect. So that no party will be harmed later. The conclusion drawn from the discussion above is that the recently passed Job Creation Law can bring advantages and disadvantages to workers and laborers, especially women workers. It can be seen, in the implementation process, women workers are always neglected, they are vulnerable to violence, sexual harassment, bullying, humiliation and belittlement. Not to mention, they are the back of their family. In terms of female reproduction such as during menstruation. The Job Creation Law does not strengthen the reproductive health rights of women workers which were not previously fulfilled in the old law. Even though it should be, in terms of law reform, the Job Creation Law should have strengthened small rights like this. However, in reality, there is also no law that can be a solution to this problem. For this reason, many trade union alliances and women's unions oppose the passing of the Job Creation Law.